A multidisciplinary approach toward the replacement of missing maxillary anterior teeth using impacted mesiodens as abutment via "reverse endodontic treatment" - Sunandan Mittal; Vivek Aggarwal; Sudhir Munjal; Tarun Kumar; Vanita Keshav; Anmolpreet Kaur; Arshpreet Kaur (Wolters Kluwer Medknow Publications, 2022)
The case report presents the rehabilitation of a missing maxillary anterior tooth. The case was complicated by the presence of an inverted, impacted mesiodens, which led to the impaction of the permanent maxillary central incisor. The apical area of the mesiodens was surgically exposed, and the endodontic treatment was carried out via the root apex in an apicocoronal direction. The case was restored with an angulated post-core crown. This case highlights an unusual placement of mesiodens and its challenging endodontic rehabilitation.